Reduction of die wear and structural defects of railway screw spike heads estimated by FEM - Alcázar, J. (2021)
Railway spike screws are manufactured by hot forging on a massive scale, due to each kilometer of railway track needing 8600 spike screws. These components have a low market value, so the head must be formed in a single die stroke. The service life of the dies is directly related to the amount of energy required to form a single screw. The existing standard for spike screws specifies only the required tolerances for the head dimensions, particularly the angle of the hub faces and the radius of agreement of the hub with the cap. Both geometrical variables of the head and process conditions (as-received material diameter and flash thickness) are critical parameters in spike production. This work focuses on minimizing the energy required for forming the head of a railway spike screw by computational simulation. The variables with the highest degree of incidence on the energy, forging load, and filling of the die are ordered statistically. The results show that flash thickness is the variable with the most significant influence on forming energy and forming load, as well as on die filling. Specifically, the minimum forming energy was obtained for combining of a hub wall angle of 1.3◦ an as-received material diameter of 23.54 mm and a flash thickness of 2.25 mm. Flash thickness generates a lack of filling at the top vertices of the hub, although this defect does not affect the functionality of the part or its serviceability. Finally, the wear is mainly concentrated on the die splice radii, where the highest contact pressure is concentrated according to the computational simulation results.